Prevalence of Cardiovascular Diseases in a Tertiary Care Teaching Hospital - Naliganti, Chandana; Valupadas, Chandrasekhar; Akkinepally, Raghuram Rao (Indian Journal of Pharmacy Practice)
Background: Cardiovascular disease (CVD) comprises the most prevalent serious disorders in the developed and developing nations. Epidemiological studies have played an important part in the elucidation of predisposing factors for CVD and opportunities for prevention and treatment. The present study is designed retrospectively to focus on prevalence of various CVD and causes of mortality in patients admitted to cardiology unit. Materials and Methods: A retrospective epidemiological study was conducted in the Intensive Cardiac Care Unit (ICCU) of a tertiary care teaching hospital where the data was collected from January, 2013 to June, 2015 (2.5 years). The study population includes all the patients admitted to ICCU with various symptoms of CVDs. The demographic and clinical data was obtained from the records and the analysis was performed. Results: A total of 6,307 patients were admitted in ICCU with an average age of 52 years in which majority was men (58.33%). The study indicates coronary heart disease (CHD) (67.06%) was most prevalent among other CVDs and non-CVDs. A total of 592 (9.12%) deaths were noted during the study period where mortality rate was high in females (11.26%). Acute myocardial infarction (AMI) and heart failure accounted for major deaths in ICCU. Conclusion: The study observed the significant prevalence of various CVD. Based on the results we hypothesize that serological studies will be necessary to identify the specific underlying aetiology/infectious pathogenesis leading to death and prospective observational study will yield significant strength to epidemiological studies respectively.
Keywords: Cardiovascular diseases; Prevalence; Mortality; Epidemiological studies